"A way to bring my labour back to normal": An immersive sensory experience during childbirth. (September 2022) - Hadland, Miss Mariann; Holland, Sari; Taylor, Rhonda; Smyth, Wendy; Nagle, Cate
Abstract : The setting in which a woman labours, influences her birth experience. Ninety-seven percent of women in Australia give birth in conventional hospital birth suites, where medical safety often overshadows attention to psychological needs. Sensory information from the external environment can help decrease pain, fear, and stress through oxytocin-mediated neurohormonal processes. No place is this more urgently needed than in the hospital birth suite. This proof-of-concept study aimed to explore women's and midwives' experiences of using an immersive sensory experience (ISE) during labour. We installed a screen projecting nature-themed films and conducted a thematic analysis of interviews with 32 women who laboured in this setting. All the women received continuity of midwifery care from caseload midwives. Four in five women had medical or obstetric risk factors, and two-thirds had their labour induced. Semi-structured interviews were conducted with nine midwives who worked in caseload and had cared for women who used the ISE. Three themes emerged from interviews with women: 1) Serenity and calm; 2) Redirection of attention; and 3) Immersive feeling. Three themes emerged from interviews with midwives: 1) The ISE aligned with midwives' identity and birthing philosophies; 2) The ISE inspired care practices that supported physiology; and 3) The ISE improved midwives' experience of providing care. The findings are consistent with research demonstrating the effects of physical attributes of the environment on caregiver behaviour and women's experiences. Overwhelmingly these finding demonstrate that midwives, women, and their partners enjoyed the immersive experience and how it positively improved the birth setting to optimise physiological labour and birth. No safety concerns were identified, and midwives reported positive feedback from colleagues.